Electric Lights (Symphony in the Flint Hills, 2019)
Introduction: Electrifying rural communities did not happen overnight. After nearly a decade of debate, politicking, and budgeting, Strong City and Cottonwood Falls finally joined forces to secure lighting for both towns.